Study on Optimization of Irrigation Systems in Gonseng Village Megaluh District Jombang Regency - Nasirudin, Mohammad; Puspaningrum, Yessita (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
Irrigation infrastructure management from a historical perspective is closely related to national food security. In the management of facilities and infrastructure, irrigation must be able to meet the needs of farmers. Every plant needs enough air to increase agricultural productivity. Fulfilling air needs requires adequate irrigation and drainage channels in each area. One of them is Gongseng Village, which is a village located in Megaluh District, Jombang Regency. Optimizing the performance of irrigation and drainage channels in Gongseng Village requires concrete and precise steps. This irrigation and drainage literature review discusses the optimization of irrigation channel performance. All irrigation channel buildings have the same condition, where the walls of the building are overgrown with wild plants, some of the walls of the channel buildings are damaged due to the lack of structural strength of the building. The effectiveness of irrigation channels in Gongseng Village is still not optimal, because the maintenance of facilities and infrastructure is still lacking, and public knowledge is still lacking. Keyword : Optimization of irrigation, Irrigation system, Gongseng Village